The Influence of Diligence and Competence Through Motivation on The Performing of State Civil Apparatus - M. Zahari; Ali Akbar; Refki Mudasir Widyasyah (DINASTI RESEARCH, 2026)
The purpose of this scientific study is to assess how diligence and competence affect state civil servants' (ASN) motivation, motivation on Performing, diligence and competence on Performing, and diligence and competence through motivation on Performing. The General Bureau of the Regional Secretariat of Jambi Province, Indonesia, served as the study site. Both primary and secondary data were used in this investigation. 91 respondents made up the research sample. Saturated sampling was employed in the sample procedure. Both quantitative and descriptive analysis were used in the analysis process. Path study with the Partial Least Squares (PLS) method was employed in the quantitative studY, Software called SmartPLS 4.0 was used to help process data. The outcomes demonstrated that motivation was positively and significantly impacted by competence and diligence. Competence significantly and favorably affected ASN Performing, whereas diligence had no discernible impact. The impact of motivation on ASN Performing was both positive and significant. ASN Performing at the General Bureau of the Jambi Province Regional Secretariat was positively and significantly impacted by diligence and competence through incentive.